2017
DOI: 10.3892/ijo.2017.3947
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-10b mediates TGF-β1-regulated glioblastoma proliferation, migration and epithelial-mesenchymal transition

Abstract: Although it is well known that exaggerated proliferation, metastasis and the mesenchymal subtype is related with worst prognoses in glioblastoma (GBM) and that transforming growth factor-β1 (TGF-β1) is a potent factor in regulating the proliferation, migration and epithelial-mesenchymal transition (EMT) phenotype of GBM, the detailed mechanisms are still far from elucidated. MicroRNAs (miRNAs) are small non-coding RNAs which play critical roles in various diseases by regulating target gene expression. We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…In tumors, TGF-β, once activated, promotes cell growth, migration and invasion (29,30), therefore, the level of TGF-β expression in tumors is also related to the degree of malignancy of the tumor. A previous study demonstrated that TGF-β promotes the migration of human glioma cells by promoting the expression of miR-10b (31). In the present study, it was demonstrated that the proliferation of esophageal cancer cells increased along with an increase of TGF-β concentration.…”
Section: Discussionsupporting
confidence: 65%
“…In tumors, TGF-β, once activated, promotes cell growth, migration and invasion (29,30), therefore, the level of TGF-β expression in tumors is also related to the degree of malignancy of the tumor. A previous study demonstrated that TGF-β promotes the migration of human glioma cells by promoting the expression of miR-10b (31). In the present study, it was demonstrated that the proliferation of esophageal cancer cells increased along with an increase of TGF-β concentration.…”
Section: Discussionsupporting
confidence: 65%
“…The pleiotropic nature of microRNA-10b was due to its suppression of multiple tumor suppressors, including ras homolog family member C (RhoC), urokinase plasminogen activator receptor (uPAR), matrix metalloproteinases (MMPs), tumor protein p53 (TP53), forkhead box O3 (FOXO3), CYLD lysine 63 deubiquitinase (CYLD), paired box 6 (PAX6), patched 1 (PTCH1), homeobox D10 (HOXD10), notch receptor 1 (NOTCH1), BCL6 transcription repressor (Bcl-6), and Kruppel like factor 4 (KLF4) [29][30][31][32][33]. A recent study reported that microRNA-10b mediated transforming growth factor-β1-regulated glioblastoma proliferation, migration, and epithelial-mesenchymal transition (EMT) [34].…”
Section: Introductionmentioning
confidence: 99%
“…This multifunctional cytokine of the transforming growth factor b family has been implicated in immunomodulation, proliferation, migration, and epithelial-mesenchymal transition (EMT) of tumor cells [ 18 ]. TGFB1 is also a well-known factor capable of increasing GBM cell proliferation and migration [ 19 22 ]. Given that autocrine TGFB1 signaling is essential to sustain stemness and high tumorigenicity of GBM-initiating cells [ 23 ], possible paracrine effects of cytokines released by resident MSC in the tumor stroma must be addressed.…”
Section: Introductionmentioning
confidence: 99%